MOF composite material for adsorbing micromolecular VOCs and preparation method thereof

Through the synergistic action of modified MOF, modified bacterial cellulose and modified graphene oxide, MOF composite materials are formed, which solves the problems of limited adsorption of small molecule VOCs and poor stability in humid environments, and achieves efficient adsorption and stability improvement.

CN119869481APending Publication Date: 2025-04-25DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510226212.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing MOF materials have limited adsorption amounts of small molecule VOCs and have poor stability in humid environments, resulting in a decrease in adsorption efficiency and reduced application durability.

Method used

The MOF composite material is formed through the synergy between modified MOF, modified bacterial cellulose and modified graphene oxide. Modified MOF is modified by titanium-based and copper-based composite modification, modified bacterial cellulose introduces epoxy groups, and modified graphene oxide introduces amino groups to improve the adsorption efficiency and structural stability of the material.

Benefits of technology

The adsorption amount of small molecule VOCs is significantly improved, and the stability and application durability of materials are improved in humidity environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of adsorption and recovery of VOCs (volatile organic compounds), in particular to an MOF (metal organic framework) composite material for adsorbing micromolecular VOCs and a preparation method thereof. Comprising the following steps: adding modified MOF, modified bacterial cellulose and modified graphene oxide into an N, N-dimethylformamide aqueous solution, and stirring for 1-2 days; transferring into a polytetrafluoroethylene reaction kettle, carrying out hydrothermal reaction at 160-200 DEG C for 6-16 hours, cooling, carrying out centrifugal filtration, soaking in methanol for 1-3 days, and drying; therefore, the MOF composite material for adsorbing the micromolecular VOCs is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of VOCs adsorption and recovery, and in particular to a MOF composite material for adsorbing small molecule VOCs and a preparation method thereof. Background Art

[0002] With the continuous development of industrialization, volatile organic compounds (VOCs) have become one of the main sources of air pollution. Especially in the chemical production process, the emission of VOCs has posed a serious threat to the environment and human health. In order to reduce the concentration of VOCs, many methods have been proposed, including adsorption, catalytic oxidation, condensation, etc. As an efficient, economical and environmentally friendly VOCs treatment technology, adsorption has received widespread attention.

[0003] Adsorption materials are one of the most convenient means for VOCs treatment; among them, the selection of adsorption materials is one of the key factors to improve adsorption efficiency. In recent years, metal organic framework materials (MOF) are a new type of material with high specific surface area and adjustable pore structure; it has adsorption properties for small molecule VOCs such as low boiling point and strong polarity; therefore, it has become a research hotspot. In the prior art, common small molecule VOCs include ethyl acetate, toluene and other substances, but the existing MOFs materials have limited adsorption capacity for small molecule VOCs. On the other hand, MOFs materials have poor stability. Due to the action of water molecules in a humid environment, it will cause structural collapse in this environment, resulting in reduced adsorption efficiency and reduced application durability.

[0004] In summary, it is of great significance to solve the above problems and prepare a MOF composite material for adsorbing small molecule VOCs. Summary of the invention

[0005] The object of the present invention is to provide a MOF composite material for adsorbing small molecule VOCs and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a MOF composite material for adsorbing small molecule VOCs comprises the following steps: The modified MOF, modified bacterial cellulose and modified graphene oxide are added to an N,N-dimethylformamide aqueous solution and stirred for 1 to 2 days; the mixture is transferred to a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 160 to 200°C for 6 to 16 hours, cooled, centrifugally filtered, immersed in methanol for 1 to 3 days, and dried to obtain a MOF composite material.

[0007] More optimally, the raw materials of the MOF composite material include modified graphene oxide, modified MOF, and modified bacterial cellulose in a mass ratio of 0.05~0.2:1:0.05~0.2.

[0008] More optimally, the preparation method of the modified MOF is: S1-1: adding zirconium tetrachloride, 1,4-phthalic acid, benzoic acid, and 2-aminoterephthalic acid in a molar ratio of 1:1:1-2:0.8-1 to a 95wt%-96wt% N,N-dimethylformamide aqueous solution and reacting at 90-100°C for 6-16 hours to obtain MOF; S1-2: MOF, titanium tetrachloride and copper chloride are added to N,N-dimethylformamide in sequence, and stirred at 70-85° C. for 5-7 days to obtain modified MOF.

[0009] More optimally, the raw materials of the modified MOF include MOF, titanium tetrachloride and copper chloride in a mass ratio of 6-9:1-2:1-1.5.

[0010] In a further embodiment, the graphene oxide is carboxylated graphene with an equivalent particle size of about 0.5 μm-5 μm and a carboxyl content of 4.0 wt%.

[0011] More optimally, the preparation method of the modified graphene oxide is: S2-1: Disperse graphene oxide in deionized water, add 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, react at 40-80° C. for 4-8 hours, wash, and dry to obtain modified graphene oxide.

[0012] More optimally, the raw materials of the modified graphene oxide include graphene oxide, 3-aminopropyltriethoxysilane, and dicyclohexylcarbodiimide in a mass ratio of 1-2:1-3:0.01-0.05.

[0013] More optimally, the preparation method of the modified bacterial cellulose is: S3-1: adding bacterial cellulose to a 25wt% to 35wt% sodium hydroxide aqueous solution, alkalizing at 25 to 35°C for 1 to 2 hours, washing, and drying to obtain alkalized bacterial cellulose; S3-2: Add alkalized bacterial cellulose, epichlorohydrin, and 5wt%~15wt% potassium hydroxide aqueous solution to ethanol, react at 25~35°C for 6~12 hours, wash, filter, and dry to obtain modified bacterial cellulose.

[0014] More optimally, the raw materials of the modified bacterial cellulose include, by weight, 2 to 5 parts of alkalized bacterial cellulose, 4 to 8 parts of epichlorohydrin, 0.2 to 0.5 parts of 5wt% to 15wt% potassium hydroxide aqueous solution, and 50 to 60 parts of ethanol.

[0015] Compared with the prior art, the beneficial effects of the present invention are: a modified MOF with a bimetallic center is obtained by modification, and a MOF composite material is formed by synergistically modifying bacterial cellulose and modified graphene oxide, which effectively improves the stability of MOF while increasing the adsorption amount of small molecule VOCs, thereby increasing its applicability in a humid environment and increasing its application durability.

[0016] In the scheme, the modified MOF adopts titanium-based and copper-based composite modified MOF, and uses specific bimetallic centers to promote the interface between small molecule VOCs and materials, promote the adsorption of small molecule gases such as ethyl acetate, and improve the adsorption efficiency. Among them, titanium ions and copper ions can form a synergistic effect with organic ligands, greatly improving the adsorption efficiency. Titanium ions can improve separation performance, accelerate the rate of gas diffusion to the MOF pore size, and enable more VOCs small molecules to contact the adsorption site; copper ions can have a stronger targeting for the adsorption of ethyl acetate small molecules. In addition, copper ions have a certain hydration ability, which can enhance the hydrophilicity of MOF composite materials and further improve water stability.

[0017] However, titanium-based and copper-based modification of MOF will cause changes in the original structure, resulting in structural instability and easy collapse, which greatly affects the actual adsorption effect.

[0018] In the scheme, amino groups are introduced into modified graphene oxide. Since graphene oxide itself has a two-dimensional layered structure and contains a large number of oxygen-containing functional groups on its surface, it can provide more active sites and enhance the adsorption efficiency after modification. On the other hand, its introduction can produce an interface effect with the modified MOF and be loaded on its surface, further improving the structural stability.

[0019] In the scheme, epoxy groups are introduced into modified bacterial cellulose. Since bacterial cellulose itself has a framework structure and is porous, it can adsorb gases. At the same time, after modification, it has more active sites, which enhances the adsorption capacity of small molecule VOCs. On the one hand, its introduction can produce an interfacial effect with the modified MOF through hydrogen bonding and be loaded on its surface, thereby reducing the phenolization of the MOFs material and improving its structural stability. On the other hand, the modified bacterial cellulose can react with the modified graphene oxide through the epoxyamino group to produce an interfacial effect, further synergistically improving the stability of the MOF composite material and improving the adsorption efficiency. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] It should be noted that the following parts are parts by mass, and all raw material purchasing manufacturers involved in the present invention are not subject to any special restrictions. Examples include: In the following embodiments, graphene oxide is carboxylated graphene with an equivalent particle size of 0.5 μm to 5 μm and a carboxyl content of 4.0 wt%.

[0022] Example 1: A method for preparing a MOF composite material for adsorbing small molecule VOCs, comprising the following steps: Step 1: S1: Add zirconium tetrachloride, 1.4-phthalic acid, benzoic acid, and 2-hydroterephthalic acid in a molar ratio of 1:1:1.5:0.9 to a 95wt% N,N-dimethylformamide aqueous solution and react at 95°C for 12 hours to obtain MOF; S2: Add MOF, titanium tetrachloride, and copper chloride in a mass ratio of 7.5:1.5:1.2 to N,N-dimethylformamide in sequence, and stir at 78°C for 6 days to obtain a modified MOF; Step 2: dispersing graphene oxide in deionized water, adding 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, the mass ratio of graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide is 1.5:2:0.03, reacting at 60°C for 6 hours, washing, and drying to obtain modified graphene oxide; Step 3: S1: adding bacterial cellulose to a 30 wt % sodium hydroxide aqueous solution, alkalizing at 30° C. for 1.5 hours, washing, and drying to obtain alkalized bacterial cellulose; S2: adding 3.5 parts of alkalized bacterial cellulose, 6 parts of epichlorohydrin, and 0.35 parts of a 10 wt % potassium hydroxide aqueous solution to 55 parts of ethanol, reacting at 30° C. for 9 hours, washing, filtering, and drying to obtain modified bacterial cellulose; Step 4: Add modified MOF, modified bacterial cellulose and modified graphene oxide in a mass ratio of 1:0.1:0.12 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0023] Example 2: A method for preparing a MOF composite material for adsorbing small molecule VOCs, comprising the following steps: Step 1: S1: Add zirconium tetrachloride, 1.4-phthalic acid, benzoic acid, and 2-hydroterephthalic acid in a molar ratio of 1:1:1:0.8 to a 95wt% N,N-dimethylformamide aqueous solution and react at 95°C for 12 hours to obtain MOF; S2: Add MOF, titanium tetrachloride, and copper chloride in a mass ratio of 6:1:1 to N,N-dimethylformamide in sequence, and stir at 78°C for 6 days to obtain a modified MOF; Step 2: dispersing graphene oxide in deionized water, adding 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, the mass ratio of graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide is 1:1:0.01, reacting at 60°C for 6 hours, washing, and drying to obtain modified graphene oxide; Step 3: S1: adding bacterial cellulose to a 30wt% sodium hydroxide aqueous solution, alkalizing at 30°C for 1.5 hours, washing and drying to obtain alkalized bacterial cellulose; S2: adding 2 parts of alkalized bacterial cellulose, 4 parts of epichlorohydrin, and 0.2 parts of a 10wt% potassium hydroxide aqueous solution to 55 parts of ethanol, reacting at 30°C for 9 hours, washing, filtering, and drying to obtain modified bacterial cellulose; Step 4: Add modified MOF, modified bacterial cellulose and modified graphene oxide in a mass ratio of 1:0.05:0.05 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0024] Example 3: A method for preparing a MOF composite material for adsorbing small molecule VOCs, comprising the following steps: Step 1: S1: Add zirconium tetrachloride, 1.4-phthalic acid, benzoic acid, and 2-hydroterephthalic acid in a molar ratio of 1:1:2:1 to a 95wt% N,N-dimethylformamide aqueous solution and react at 95°C for 12 hours to obtain MOF; S2: Add MOF, titanium tetrachloride, and copper chloride in a mass ratio of 9:2:1.5 to N,N-dimethylformamide in sequence, and stir at 78°C for 6 days to obtain a modified MOF; Step 2: dispersing graphene oxide in deionized water, adding 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, the mass ratio of graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide is 2:3:0.05, reacting at 60°C for 6 hours, washing, and drying to obtain modified graphene oxide; Step 3: S1: adding bacterial cellulose to a 30 wt % sodium hydroxide aqueous solution, alkalizing at 30° C. for 1.5 hours, washing, and drying to obtain alkalized bacterial cellulose; S2: adding 5 parts of alkalized bacterial cellulose, 8 parts of epichlorohydrin, and 0.5 parts of a 10 wt % potassium hydroxide aqueous solution to 55 parts of ethanol, reacting at 30° C. for 9 hours, washing, filtering, and drying to obtain modified bacterial cellulose; Step 4: Add modified MOF, modified bacterial cellulose and modified graphene oxide in a mass ratio of 1:0.2:0.2 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0025] Comparative Example 1: Based on Example 1, graphene oxide is used instead of modified graphene oxide, and the other processes remain unchanged, specifically: Step 1: S1: Add zirconium tetrachloride, 1.4-phthalic acid, benzoic acid, and 2-hydroterephthalic acid in a molar ratio of 1:1:1.5:0.9 to a 95wt% N,N-dimethylformamide aqueous solution and react at 95°C for 12 hours to obtain MOF; S2: Add MOF, titanium tetrachloride, and copper chloride in a mass ratio of 7.5:1.5:1.2 to N,N-dimethylformamide in sequence, and stir at 78°C for 6 days to obtain a modified MOF; Step 2: S1: adding bacterial cellulose to a 30 wt % sodium hydroxide aqueous solution, alkalizing at 30° C. for 1.5 hours, washing, and drying to obtain alkalized bacterial cellulose; S2: adding 3.5 parts of alkalized bacterial cellulose, 6 parts of epichlorohydrin, and 0.35 parts of a 10 wt % potassium hydroxide aqueous solution to 55 parts of ethanol, reacting at 30° C. for 9 hours, washing, filtering, and drying to obtain modified bacterial cellulose; Step 3: Add modified MOF, modified bacterial cellulose and graphene oxide in a mass ratio of 1:0.1:0.15 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0026] Comparative Example 2: Based on Example 1, UiO-66 MOF in the prior art is used as the substrate structure, and the other processes remain unchanged, specifically: Step 1: dispersing graphene oxide in deionized water, adding 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, the mass ratio of graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide is 1.5:2:0.03, reacting at 60°C for 6 hours, washing, and drying to obtain modified graphene oxide; Step 2: S1: adding bacterial cellulose to a 30 wt % sodium hydroxide aqueous solution, alkalizing at 30° C. for 1.5 hours, washing, and drying to obtain alkalized bacterial cellulose; S2: adding 3.5 parts of alkalized bacterial cellulose, 6 parts of epichlorohydrin, and 0.35 parts of a 10 wt % potassium hydroxide aqueous solution to 55 parts of ethanol, reacting at 30° C. for 9 hours, washing, filtering, and drying to obtain modified bacterial cellulose; Step 3: Add UiO-66 MOF, modified bacterial cellulose and modified graphene oxide in a mass ratio of 1.2:0.1:0.12 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0027] Comparative Example 3: Based on Example 1, the ratio of titanium base, copper base and MOF was changed, and the other processes remained unchanged, specifically: Step 1: S1: Add zirconium tetrachloride, 1,4-phthalic acid, benzoic acid, and 2-hydroterephthalic acid in a molar ratio of 1:1:1.5:0.9 to a 95wt% N,N-dimethylformamide aqueous solution and react at 95°C for 12 hours to obtain MOF; S2: Add MOF, titanium tetrachloride, and copper chloride in a mass ratio of 10:0.5:0.2 to N,N-dimethylformamide in sequence, and stir at 78°C for 6 days to obtain a modified MOF; Step 2: dispersing graphene oxide in deionized water, adding 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, the mass ratio of graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide is 1.5:2:0.03, reacting at 60°C for 6 hours, washing, and drying to obtain modified graphene oxide; Step 3: S1: adding bacterial cellulose to a 30 wt % sodium hydroxide aqueous solution, alkalizing at 30° C. for 1.5 hours, washing, and drying to obtain alkalized bacterial cellulose; S2: adding 3.5 parts of alkalized bacterial cellulose, 6 parts of epichlorohydrin, and 0.35 parts of a 10 wt % potassium hydroxide aqueous solution to 55 parts of ethanol, reacting at 30° C. for 9 hours, washing, filtering, and drying to obtain modified bacterial cellulose; Step 4: Add modified MOF, modified bacterial cellulose and modified graphene oxide in a mass ratio of 1:0.1:0.12 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0028] Comparative Example 4: Based on Example 1, modified bacterial cellulose is not introduced, and the other processes remain unchanged, specifically: Step 1: S1: Add zirconium tetrachloride, 1.4-phthalic acid, benzoic acid, and 2-hydroterephthalic acid in a molar ratio of 1:1:1.5:0.9 to a 95wt% N,N-dimethylformamide aqueous solution and react at 95°C for 12 hours to obtain MOF; S2: Add MOF, titanium tetrachloride, and copper chloride in a mass ratio of 7.5:1.5:1.2 to N,N-dimethylformamide in sequence, and stir at 78°C for 6 days to obtain a modified MOF; Step 2: dispersing graphene oxide in deionized water, adding 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, the mass ratio of graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide is 1.5:2:0.03, reacting at 60°C for 6 hours, washing, and drying to obtain modified graphene oxide; Step 3: Add the modified MOF and modified graphene oxide in a mass ratio of 1:0.15 to an N,N-dimethylformamide aqueous solution and stir for 1.5 days; transfer to a polytetrafluoroethylene reactor, perform a hydrothermal reaction at 180°C for 11 hours, cool, centrifuge and filter, soak in methanol for 2 days, and dry to obtain a MOF composite material.

[0029] Testing experiment: The performance of the MOF composite material for adsorbing small molecule VOCs prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested: Adsorption rate test: (1) The MOF composite material for adsorbing small molecule VOCs prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was subjected to 30,000 (mL·h -1 ·g -1 ) at 30 ° C, the adsorption of ethyl acetate was carried out, and the adsorption results are shown in Table 1; (2) The MOF composite material for adsorbing small molecule VOCs prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was subjected to 30000 (mL·h -1 ·g -1 ) The adsorption of ethyl acetate was carried out at 30 °C, and the results of the adsorption amount are shown in Table 1; Examples Adsorption amount at 0% humidity (mg·g-1) Adsorption capacity at 80% humidity (mg·g-1) Example 1 219.98 154.91 Example 2 218.44 153.88 Example 3 218.12 153.96 Comparative Example 1 211.16 142.11 Comparative Example 2 200.76 131.16 Comparative Example 3 196.11 127.22 Comparative Example 4 205.12 139.77 Table 1 Result analysis: According to the data analysis of Table 1, it can be seen from Examples 1 to 3 that the present application has prepared a MOF composite material with good adsorption efficiency, structural stability, and good stability at a certain humidity. From the data of Comparative Examples 1 to 4, it can be seen that the data of Comparative Example 1 shows that replacing modified graphene oxide with graphene oxide mainly affects the structural stability and partial synergy of the material, affecting the overall performance. From the data of Comparative Example 2, it can be seen that the UiO-66MOF in the prior art is used as the base structure, and the design of improving water stability by titanium-based and copper-based composite modified MOF in the present invention is completely abandoned, affecting the material's tolerance to water vapor and the adsorption efficiency of ethyl acetate. From the data of Comparative Example 3, it can be seen that changing the ratio of titanium-based, copper-based and MOF reduces the synergy originally formed by titanium ions, copper ions and organic ligands in the modified MOF, thereby affecting the material's tolerance to water vapor. From the data of Comparative Example 4, it can be seen that without introducing modified bacterial cellulose, the overall synergy of the composite material is weakened, the structural stability and active sites are reduced, and the overall performance is reduced.

[0030] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a MOF composite material for adsorbing small molecule VOCs, characterized in that: The following steps are involved: The modified MOF, modified bacterial cellulose and modified graphene oxide are added to an N,N-dimethylformamide aqueous solution and stirred for 1 to 2 days; the mixture is transferred to a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 160 to 200°C for 6 to 16 hours, cooled, centrifugally filtered, immersed in methanol for 1 to 3 days, and dried to obtain a MOF composite material.

2. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 1, characterized in that: The raw materials of the MOF composite material include modified graphene oxide, modified MOF and modified bacterial cellulose in a mass ratio of 0.05-0.2:1:0.05-0.

2.

3. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 2, characterized in that: The preparation method of the modified MOF is: S1-1: adding zirconium tetrachloride, 1,4-phthalic acid, benzoic acid, and 2-aminoterephthalic acid in a molar ratio of 1:1:1-2:0.8-1 to a 95wt%-96wt% N,N-dimethylformamide aqueous solution and reacting at 90-100°C for 6-16 hours to obtain MOF; S1-2: MOF, titanium tetrachloride and copper chloride are added to N,N-dimethylformamide in sequence, and stirred at 70-85° C. for 5-7 days to obtain modified MOF.

4. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 3, characterized in that: The raw materials of the modified MOF include MOF, titanium tetrachloride and copper chloride in a mass ratio of 6-9:1-2:1-1.

5.

5. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 2, characterized in that: The preparation method of the modified graphene oxide is: S2-1: Disperse graphene oxide in deionized water, add 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide, react at 40-80° C. for 4-8 hours, wash, and dry to obtain modified graphene oxide.

6. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 5, characterized in that: The raw materials of the modified graphene oxide include graphene oxide, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide in a mass ratio of 1-2:1-3:0.01-0.

05.

7. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 2, characterized in that: The preparation method of the modified bacterial cellulose is: S3-1: adding bacterial cellulose to a 25wt% to 35wt% sodium hydroxide aqueous solution, alkalizing at 25 to 35°C for 1 to 2 hours, washing, and drying to obtain alkalized bacterial cellulose; S3-2: Add alkalized bacterial cellulose, epichlorohydrin, and 5wt%~15wt% potassium hydroxide aqueous solution to ethanol, react at 25~35°C for 6~12 hours, wash, filter, and dry to obtain modified bacterial cellulose.

8. The method for preparing a MOF composite material for adsorbing small molecule VOCs according to claim 7, characterized in that: The raw materials of the modified bacterial cellulose include, by weight, 2 to 5 parts of alkalized bacterial cellulose, 4 to 8 parts of epichlorohydrin, 0.2 to 0.5 parts of 5wt% to 15wt% potassium hydroxide aqueous solution, and 50 to 60 parts of ethanol.

9. The MOF composite material prepared according to the method for preparing a MOF composite material for adsorbing small molecule VOCs according to any one of claims 1 to 8.